The effectiveness of direct corners in high level soccer depending on the type and the zone of delivery - Plakias, S.; Kokkotis, C.; Tsaopoulos, D.; Moustakidis, S.; Papalexi, M.; Giakas, G.; Tsatalas, T. (Journal of Physical Education and Sport, 2023)
Sports analytics and performance analysis in general have a great contribution to improving the performance of soccer players and teams. The efficiency in corners is crucial for the final result of a soccer game. For this reason, the corners are widely studied by both team analysts and researchers. This study analyzed the corners that were executed directly (i.e., corners that were not executed with a short pass) in the Greek Super League 2020-21. The sample consisted of 1709 direct corners that were performed during the championship (N = 240 games). Statistical analyses were performed and employed log-linear analysis and the chi-square test. The obtained results showed that the percentage of out-swinging corners ending in a final effort was statistically significantly higher than the percentage of in-swinging corners, but there was no statistically significant difference in the respective percentages of corners that ended in goals. The results also showed that the percentage of counterattacks was statistically significantly higher for the corners executed in the goalkeeping (Gk) zone compared to the corners executed in the 1st post (nearest to the corner kick). In addition, the percentage of final attempts in the 2nd post and the penalty zone were significantly higher than the percentage of final attempts in the 1st post, while the percentage of final attempts in the penalty zone was significantly higher than the corresponding percentage in the Gk zone. The research findings can be used by coaches to improve the efficiency of their team while executing corners, both during the defense and in the attack phase.